Evaluating the potency of laser-activated antimicrobial photodynamic therapy utilizing methylene blue as a treatment approach for chronic periodontitis - Karuppan Perumal, Manoj Kumar; Rajan Renuka, Remya; Manickam Natarajan, Prabhu (Frontiers in Oral Health, 2024)
Chronic periodontitis is a ubiquitous inflammatory disease in dental healthcare that is challenging to treat due to its impact on bone and tooth loss. Conventional mechanical debridement has been challenging in eliminating complex subgingival biofilms. Hence, adjunctive approaches like low-level laser antimicrobial photodynamic therapy (A-PDT) utilising methylene blue (MB) have been emerging approaches in recent times. This review evaluates the latest research on the use of MB-mediated A-PDT to decrease microbial count and enhance clinical results in chronic periodontitis. Studies have shown the interaction between laser light and MB generates a phototoxic effect thereby, eliminating pathogenic bacteria within periodontal pockets. Moreover, numerous clinical trials have shown that A-PDT using MB can reduce probing depths, improve clinical attachment levels, and decrease bleeding during probing in comparison to traditional treatment approaches. Notably, A-PDT shows superior antibiotic resistance compared to conventional antibiotic treatments. In conclusion, the A-PDT using MB shows promise as an adjunctive treatment for chronic periodontitis. Additional research is required to standardize treatment protocols and assess long-term outcomes of A-PDT with MB in the treatment of periodontitis.